If zy < xy < 0 is |x-z| + |x| = |z| : GMAT Data Sufficiency (DS)
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 21 Jan 2017, 06:51

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# If zy < xy < 0 is |x-z| + |x| = |z|

Author Message
TAGS:

### Hide Tags

Intern
Joined: 25 Oct 2009
Posts: 6
Followers: 0

Kudos [?]: 0 [0], given: 0

If zy < xy < 0 is |x-z| + |x| = |z| [#permalink]

### Show Tags

17 Jan 2010, 10:42
3
This post was
BOOKMARKED
00:00

Difficulty:

85% (hard)

Question Stats:

52% (02:19) correct 48% (01:34) wrong based on 88 sessions

### HideShow timer Statistics

If zy < xy < 0 is |x-z| + |x| = |z|

(1) z < x
(2) y > 0
[Reveal] Spoiler: OA
Manager
Joined: 27 Apr 2008
Posts: 190
Followers: 1

Kudos [?]: 77 [0], given: 1

### Show Tags

17 Jan 2010, 10:48
This should be asked in the DS forum.
Math Expert
Joined: 02 Sep 2009
Posts: 36590
Followers: 7090

Kudos [?]: 93320 [1] , given: 10557

### Show Tags

17 Jan 2010, 13:14
1
KUDOS
Expert's post
bharat2384 wrote:
If zy<xy<0 is |x-z|+|x|=|z|
1.z<x
2.y>0

This question was discussed before here is my post from there:

This is not a good question, as neither of statement is needed to answer the question, stem is enough to do so.

If $$zy<xy<0$$ is $$|x-z|+|x| = |z|$$

Look at the inequality $$zy<xy<0$$:

We can have two cases:

A. If $$y<0$$ --> when reducing we should flip signs and we'll get: $$z>x>0$$.
In this case: as $$z>x$$ --> $$|x-z|=-x+z$$; as $$x>0$$ and $$z>0$$ --> $$|x|=x$$ and $$|z|=z$$.

Hence in this case $$|x-z|+|x|=|z|$$ will expand as follows: $$-x+z+x=z$$ --> $$0=0$$, which is true.

And:

B. If $$y>0$$ --> when reducing we'll get: $$z<x<0$$.
In this case: as $$z<x$$ --> $$|x-z|=x-z$$; as $$x<0$$ and $$z<0$$ --> $$|x|=-x$$ and $$|z|=-z$$.

Hence in this case $$|x-z|+|x|=|z|$$ will expand as follows: $$x-z-x=-z$$ --> $$0=0$$, which is true.

So knowing that $$zy<xy<0$$ is true, we can conclude that $$|x-z|+|x| = |z|$$ will also be true. Answer should be D even not considering the statements themselves.

As for the statements:

Statement (1) says that $$z<x$$, hence we have case B.

Statement (2) says that $$y>0$$, again we have case B.

Hope it helps.
_________________
Intern
Joined: 11 Dec 2012
Posts: 35
Followers: 0

Kudos [?]: 0 [0], given: 59

Re: If zy<xy<0 is |x-z|+|x|=|z| 1.z<x 2.y>0 A. [#permalink]

### Show Tags

09 Jan 2013, 10:30
If zy<xy<0 is |x-z|+|x|=|z|
1.z<x
2.y>0

A. Statement (1) ALONE is sufficient, but statement (2) alone is not sufficient.
B. Statement (2) ALONE is sufficient, but statement (1) alone is not sufficient.
C. BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is
sufficient.
D. EACH statement ALONE is sufficient.
E. Statements (1) and (2) TOGETHER are NOT sufficient.

Bunuel is right we don't need stmts (1) or (2) or both to solve this problem. Here how can we come to it.

squre both sides of the equation:

|x-z|+|x|=|z|
|x-z|=|z|-|x|
x^2-2xz+z^2=x^2-2|xz|+z^2
after that we have:

-2xz=-2|xz| divding this equation by -2 we have:
xz=|xz| which means that question asks us: is xz=|xz|? here everything is clear
i.e.If zy<xy<0 y must be positive or negative. If y positive x and z must be both negative or vice versa which means that if y is negative both x and z must be positive where the inequality zy<xy<0 will be correct.

So we don't need any statements to solve this problem
Verbal Forum Moderator
Joined: 10 Oct 2012
Posts: 630
Followers: 80

Kudos [?]: 1120 [0], given: 136

Re: If zy < xy < 0 is |x-z| + |x| = |z| [#permalink]

### Show Tags

01 Feb 2013, 04:57
Given that zy < xy < 0 . Thus, xy-zy>0 = y(x-z)>0.

(1) z < x . Thus, from above y has to be positive. Hence, sufficient.

(2) y > 0. Similarly from above, (x-z)>0. Also sufficient.

D.
_________________
Intern
Joined: 12 Dec 2012
Posts: 2
Followers: 0

Kudos [?]: 0 [0], given: 2

Re: If zy < xy < 0 is |x-z| + |x| = |z| [#permalink]

### Show Tags

05 Feb 2013, 23:20
zy<xy<0 (for y<0).....z..................x...................|..................x..................z....(for y>0)

so |x-z| + |x| = |z| -----> |delta| + |x| = |z| -------> LHS=RHS (take a look at the no. line i have drawn above)
This is a conditional identity and will always hold true
Re: If zy < xy < 0 is |x-z| + |x| = |z|   [#permalink] 05 Feb 2013, 23:20
Similar topics Replies Last post
Similar
Topics:
6 If zy < xy < 0 is |x - z| + |x| = |z| 16 26 Nov 2011, 09:10
75 If zy < xy < 0, is | x - z | + |x| = |z|? 25 17 Sep 2010, 11:10
35 If zy < xy < 0, is |x-z| + |x| = |z|? 9 28 Jan 2010, 01:50
If zy < xy < 0, is abs(x - z) + abs(x) = abs(z)? (1) z 4 01 Jun 2008, 04:47
5 ZY<XY<0 is |X-Z| + |x| = |Z| 14 25 Apr 2007, 03:18
Display posts from previous: Sort by